Modelling and evaluation of 2-amino-2-methyl-1-propanol (amp) based process for CO₂ capture from natural gas-fired power plant. - Osagie, Ebuwa Iyore (Cranfield University, 2018)
It is widely accepted that emissions of CO₂, which is a major greenhouse gas, are the primary cause of climate change. This has led to the development of carbon capture and storage (CCS) technologies in which CO₂ is captured from large-scale point sources such as power plants. However, retrofits of carbon capture plants result in high-efficiency penalties, which have been reported to fall in the range of 7–12% points in the case of post-combustion capture (PCC) from natural gas combined cycle (NGCC) power plants. Therefore, a reduction of these efficiency losses is a high priority in order to deploy CCS at a large scale. At the moment, chemical solvent scrubbing using amines, such as monoethanolamine (MEA), is considered as the most mature option for CO₂ capture from fossil fuel-fired power plants. However, due to high heat requirements for solvent regeneration, the use of substitute solvents has been considered. This thesis investigates the capture of CO₂ from the flue gas of a NGCC power plant using 2-amino-2-methyl-1-propanol (AMP) solvent, the aim of which was to identify and evaluate opportunities for improvement. The methodology adopted in achieving the set objectives is subdivided into three sections. Firstly, a rate-based model for AMP pilot-scale PCC plant was developed with default parameters in Aspen Plus®, validated with published experimental data, and scaled up to commercial scale. Afterwards, the AMP-based plant was retrofitted into the 474 MWe NGCC power plant model, and an economic analysis was performed with the MEA-based PCC plant used as a benchmark. Lastly, the AMP-based CO₂ capture plant with solvent storage was retrofitted into the NGCC. A thermodynamic assessment revealed that the AMP-based process resulted in 25.6% lower reboiler duty, compared to that of the MEA-based process. Regardless of the superior thermodynamic performance, the economic performance of the AMP-based process was shown to be better than that of the MEA-based process only for make-up rates below 0.03% of total flowrate in the system. Furthermore, results revealed that the process with solvent storage was found to increase the profit by approximately 1% compared to that without solvent storage. Hence, this thesis showed that the use of AMP as a solvent in chemical solvent scrubbing is a good option, but may not be the most feasible option from the economic standpoint
Keywords: Post-combustion capture; 2-amino-2-methyl-1-propanol; natural gas combined cycle; modelling and simulation; solvent storage; economic analysis